Rigid Internal Fixation for Traumatic Cranio-Cervical Dissociation in Infants and Young Children. Issue 1 (1st January 2019) - Keen, Joseph R.; Ayer, Robert E.; Taha, Asma; Zouros, Alexander
Abstract : Study Design: Retrospective review. Objective: Evaluate radiographic and clinical outcomes for infants and children, who underwent rigid occipito-cervical fixation for traumatic craniocervical dissociation (tCCD). Summary of Background Data: Traumatic craniocervical dissociation is devastating. Children are at high risk but make up a large number of survivors. Non-rigid fixation has traditionally been favored over screw and rod constructs due to inherent challenges involved with instrumenting the pediatric craniocervical junction. Therefore, outcomes for rigid occipito-cervical instrumentation in infants and young children with tCCD remain uncertain. Methods: Retrospective review of children who survived tCCD between 2006 and 2016 and underwent rigid occipito-cervical fixation. Results: Fifteen children, from 8 months to 8 years old (mean, 3.8 yr), were either a passenger (n = 11) or a pedestrian (n = 4) in a motor vehicle accident. Seven patients had weakness: five with quadriplegia, one with hemiparesis, and one with bilateral upper extremity paresis. Ten patients had concurrent C1–2 instability. At last follow-up, four patients had improved motor function: one with bilateral upper extremity paresis and one with hemiparesis regained full strength, one with quadriplegia regained function on one side while another regained function in bilateral upper extremities. All underwent rigid posterior occipito-cervical fixation, with two patients requiring additional anterior and posterior fixation at non-contiguous levels. Fourteen patients were stable on flexion-extension x-rays at a mean follow-up of 31 months (9–1 yr or longer, 7–2 yr or longer). There were no cases of deformity, growth disturbance, or subaxial instability. Conclusion: Children who survive tCCD may regain function after stabilization. Rigid internal rod and screw fixation in infants and young children safely provided long-term stability. We advocate using C2 translaminar screws to exploit the favorable anatomy of pediatric lamina to minimize the risks of occipitocervical (OC) instrumentation. Level of Evidence: 4 Abstract : Traditionally, non-rigid fixation has been utilized over rigid screw and rod constructs. This is the largest and youngest series of children, who survived traumatic craniocervical dissociation and underwent rigid internal occipito-cervical fixation. Rigid occipitocervical instrumentation with screw and rod constructs provides long-term stability.